Relationships between lung function decline and skeletal muscle and fat mass changes: a longitudinal study in healthy individuals. Issue 6 (5th October 2021) - Park, Han‐Ki; Lee, So‐Hee; Lee, Suh‐Young; Kim, Sun‐Sin; Park, Heung‐Woo
Abstract: Background: The associations between long‐term changes in body mass composition and decline in lung function in healthy adults are unknown. Methods: Using a well‐defined health check‐up database, we first assessed individual longitudinal changes in muscle mass (MM) and fat mass (FM) measured via bioelectrical impedance analyses. Then we classified the enrolled individuals into five body composition groups according to their MM index (MMI) [MM (kg)/height (m) 2 ] or FM index (FMI) [FM (kg)/height (m) 2 ] change rate quartiles. Linear mixed models adjusted for age, smoking status, height, and body mass index were used to analyse the rate of forced expiratory volume in 1 s (FEV1) decline and body composition groups. Results: A total of 15 476 middle‐aged individuals (6088 women [mean age ± standard deviation: 50.74 ± 7.44] and 9388 men [mean age ± standard deviation: 49.36 ± 6.99]) were enrolled. The mean number of measurements was 6.96 (interquartile range [IQR]: 5–9) over an average follow‐up period of 8.95 years (IQR: 6.73–11.10). Decrease in MMI was significantly associated with accelerated FEV1 decline in men only ( P = 1.7 × 10 −9 ), while increase in FMI was significantly associated with accelerated FEV1 decline in both women and men ( P = 7.9 × 10 −10 and P < 2.0 × 10 −16 respectively). Linear mixed model analyses indicated that annual increase of 0.1 kg/m 2 in MMI was related to accelerated FEV1 decline by 30.79 mL/year (95% confidence interval [CI]: 26.10 to 35.48 mL/year) in men. Annual increase of 0.1 kg/m 2 in FMI was related to accelerated FEV1 decline by 59.65 mL/year in men (95% CI: 56.84 to 62.28 mL/year) and by 22.84 mL/year in women (95% CI: 18.95 to 26.74 mL/year). In body composition analysis, we found increase in MMI was significantly associated with attenuated FEV1 decline in men only ( P = 1.7 × 10 −9 ), while increase in FMI was significantly associated with accelerated FEV1 decline in both women and men ( P = 7.9 × 10 −10 and P < 2.0 × 10 −16 respectively). Individuals characterized with gain MM combined with loss of FM were associated with the most favourable outcome (i.e. the smallest rate of decline in FEV1) in both women and men. In men, loss of FM over time is more closely related with attenuated FEV1 decline than change in MM (gain or loss). Conclusions: Change in body composition over time can be used to identify healthy middle‐aged individuals at high risk for rapid FEV1 decline.